The Experience as a Victim of Bullying and Body Image Perception in Adolescents - Viny Libing; M. Dinah Charlota Lerik; Indra Yohanes Kiling (Universitas Nusa Cendana, 2021)
This study aims to determine the relationship between experiences as victims of bullying and the perception of adolescent body image. The hypothesis of this research is that there is a positive relationship between experiences as victims of bullying and the perception of negative body image in adolescents. Participants in this study involved 100 adolescents in Kupang City aged 15-23 years (79 girls and 21 boys) who experienced bullying in the past year. The study used a quantitative approach with a modified Forms of Bullying-Victimization scale and a modified Body Satisfaction scale. Hypothesis testing with the Pearson Product Moment correlation technique shows a correlation coefficient of 0.319* with a significance level of 0.0005 (p <0.01). The results showed that there was a significant positive relationship between experiences as victims of bullying and perception of body image. This study concluded that the higher the level of bullying experienced by the victim, the higher the negative body image perception was.